The Impact of a Summer Sports Camp for Children with Visual Impairments on the Self-Efficacy of Physical Education Pre-Service Teachers: A Pilot Study - John Foley; Sara Santarossa; Daniel W. Tindall; Lauren J. Lieberman (European Federation of Adapted Physical Activity, 2020)
Training and self-confidence of the instructor are important components in the success of any inclusive physical education (PE) or recreation program. The purpose of this study was to determine if the self-efficacy toward teaching students with intellectual disabilities, physical disabilities or visual impairment in PE would increase in PE pre-service teachers working at a one-week intensive sports camp for youth with visual impairments. PE pre-service teachers (n=18) filled out the Self-Efficacy Scale for Physical Education Teacher Education Majors towards Children with Disabilities (SE-PETE-D) pre- and post-camp. SE-PETE-D measured participants' self-efficacy toward including students with disabilities. Participant's self-efficacy for teaching youth with a visual impairment scores significantly increased during camp, t(17) = 3.75, p = .002, d = 0.88. A similar pattern was observed in self-efficacy for teaching youth with an intellectual disability and physical disability, with scores also significantly increasing, t(17) = 5.32, p < .001, d = 1.25 and, t(17) = 3.83, p = .001, d = .90, respectively. Results from this study suggest teaching and learning experiences that are both practical and disability-orientated can be quite effective in increasing PE pre-service teacher's confidence working with youth with disabilities